2023
DOI: 10.51709/19951272/spring2023/8
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Brand Love, Trust, and Commitment in Fostering Consumer Satisfaction and Loyalty

Abstract: Some logistic companies faced a lot of competition. The firms need to applying specific approach to exist and competitive advantage through specific brand. Yet, few research has examined consumer satisfaction with brand awareness-based consumer loyalty. So, it is essential to undertake this study in order to comprehend how customer satisfaction and loyalty are evolving over time. This study investigates the relationship between brand loyalty, brand love, and consumers' satisfaction with Indonesian logistic and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Such brand personality attributions have a direct influence on consumers' disdain and preferences (Selby, 2004). Similarly, consumers develop an emotional attachment to a brand based on their satisfaction level with it (Thomson et al, 2005;Tijjang et al, 2023). Past research in marketing contexts has also suggested that perceived brand personality leads to consumers achieving specific emotional states (McManus et al, 2022).…”
Section: Brand Personality and Brand Hatementioning
confidence: 99%
See 1 more Smart Citation
“…Such brand personality attributions have a direct influence on consumers' disdain and preferences (Selby, 2004). Similarly, consumers develop an emotional attachment to a brand based on their satisfaction level with it (Thomson et al, 2005;Tijjang et al, 2023). Past research in marketing contexts has also suggested that perceived brand personality leads to consumers achieving specific emotional states (McManus et al, 2022).…”
Section: Brand Personality and Brand Hatementioning
confidence: 99%
“…Such brand personality attributions have a direct influence on consumers’ disdain and preferences (Selby, 2004). Similarly, consumers develop an emotional attachment to a brand based on their satisfaction level with it (Thomson et al , 2005; Tijjang et al. , 2023).…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…One significant change is observed in shopping activities [3]. Nowadays, people can easily shop online through the internet, smartphones, and e-commerce applications [4]. In the past, individuals had to go to shopping centers or supermarkets, but now everyone can shop online, and products will be delivered to their homes.…”
Section: Introductionmentioning
confidence: 99%